Modification of the sheet resistance under Ti/Al/Ni/Au Ohmic contacts on AlGaN/GaN heterostructures. (May 2018) - Spera, Monia; Miccoli, Cristina; Nigro, Raffaella Lo; Bongiorno, Corrado; Corso, Domenico; Di Franco, Salvatore; Iucolano, Ferdinando; Roccaforte, Fabrizio; Greco, Giuseppe
Abstract: This paper reports on the modification of the sheet resistance under Ti/Al/Ni/Au Ohmic contacts on AlGaN/GaN heterostructures, studied by means of Transmission Line Model (TLM) structures, morphological and structural analyses, as well as computer simulations. In particular, the contacts exhibited an Ohmic behaviour after annealing at 800 °C, with a specific contact resistance ρC = (2.4 ± 0.2) × 10 −5  Ω cm 2, which was associated to morphological and structural changes of both the metal layer and the interface. Interestingly, TLM analyses gave a value of the sheet resistance under the contact (RSK = 26.1 ± 5.0 Ω/□) significantly lower than that measured outside the metal pads (RSH = 535.5 ± 12.1 Ω/□). The structural changes observed near the metal/AlGaN interface can be responsible for this electrical modification deduced by TLM analyses. As a matter of fact, two-dimensional TCAD simulation confirmed that the sheet resistance under the contact and the two-dimensional current distribution are affected by the electrical properties of the alloyed metal/semiconductor interface.